Diagnostic Imaging of Primary Hepatic Neuroendocrine Tumors: A Case and Discussion of the Literature. (2nd September 2014) - Kellock, Trenton; Tuong, Betty; Harris, Alison C.; Yoshida, Eric
Abstract : Neuroendocrine tumors (NETs) are derived from neuroendocrine cells that are capable of producing functional peptide hormones. These tumors occur most frequently in the GI tract and lungs. GI NETs frequently metastasize into the liver, though NETs of primary hepatic origin are extremely rare. Ultrasound, CT, and MRI are typically all employed for characterization of these lesions but their appearance on diagnostic imaging can be highly variable. Reported here is an interesting case of a primary hepatic neuroendocrine tumor (PHNET), along with a discussion of the imaging characteristics of these tumors. Additionally, the current standards for definitive diagnosis and treatment of PHNETs are discussed.